2002
DOI: 10.1161/01.hyp.0000025877.23309.36
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of L-Type Ca 2+ Channels in Mesenteric and Skeletal Arteries of SHR

Abstract: Abstract-An increased Ca2ϩ influx attributed to dihydropyridine-sensitive L-type Ca 2ϩ channels has been demonstrated in mesenteric vascular smooth muscle cells of spontaneously hypertensive rats (SHR). This study examined whether an upregulation of the pore-forming ␣ 1C subunit of the L-type Ca 2ϩ channel underlies this ionic defect. With the use of mesenteric arcade arteries from 12-to 16-week-old SHR and normotensive Wistar Kyoto (WKY) rats, reverse transcriptase-polymerase chain reaction demonstrated an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
117
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 30 publications
(28 reference statements)
12
117
3
Order By: Relevance
“…2) One could suggest that the hypertensioninduced reduction in cell-to-cell communication reflects a loss of signal regeneration due to altered ion channel activity. Although past studies showed that chronic hypertension can influence the activity of K ϩ and Ca 2ϩ channels (1,24,38), such changes typically coincide with alterations in arterial reactivity to vasoactive stimuli (24,38). Interestingly, no substantive change in feed artery responsiveness to myogenic tone or to global application of phenylephrine, U-46619, or acetylcholine was observed in this investigation.…”
Section: Hypertension and Cell-to-cell Communicationcontrasting
confidence: 59%
“…2) One could suggest that the hypertensioninduced reduction in cell-to-cell communication reflects a loss of signal regeneration due to altered ion channel activity. Although past studies showed that chronic hypertension can influence the activity of K ϩ and Ca 2ϩ channels (1,24,38), such changes typically coincide with alterations in arterial reactivity to vasoactive stimuli (24,38). Interestingly, no substantive change in feed artery responsiveness to myogenic tone or to global application of phenylephrine, U-46619, or acetylcholine was observed in this investigation.…”
Section: Hypertension and Cell-to-cell Communicationcontrasting
confidence: 59%
“…The resulting increase in Ca 2+ influx raises global [Ca 2+ ] i , which causes vasoconstriction and hence contributes to increased arterial pressure. It is important to note that expression of L-type Ca 2+ channels is reportedly higher in vascular smooth muscle cells of HT than in NT animals (33)(34)(35) This is the first study to examine the role of RyR-BK channel communication and the subunit composition of BK channels in HT vascular smooth muscle. However, the Ca 2+ sensitivity of single BK channels in smooth muscle of cerebral arteries and the aorta from spontaneously hypertensive rats (SHR), a genetic model of hypertension, has been previously investigated (32,36).…”
Section: Discussionmentioning
confidence: 91%
“…Several attempts have been made to explain these unique features. In hypertension, there is an increase of reactivity to vasoconstrictors, which is not only due to a higher number of L-type Ca 2+ channels (Godfraind, 2005;Pesic et al, 2004;Pratt et al, 2002), but also to depolarization of the resting potential of hypertensive VSMCs (Morel & Godfraind, 1994;Pesic et al, 2004). Depolarization leads to an increased proportion L-type Ca 2+ channels in the inactivated state, which according to the "modulated receptor theory" may have higher affinity to CaBs than channels in the resting state (Bean et al, 1986;Godfraind, 2005;Morel & Godfraind, 1987).…”
Section: Discussionmentioning
confidence: 99%